A portfolio balance approach to monetary and fiscal-policies in a small open-economy - Thom, Dr (Economic & Social Studies, 1980)
Monetary and fiscal policies are examined in a steady-state small open economy model. Complete price taking behaviour implies that domestic output is supply determined and invariant to domestic shocks. Balanced budget fiscal policy does, however, alter equilibrium real disposable income. As the terms of trade do not vary with the exchange rate regime the effectiveness of macro policies are similar under both fixed and flexible exchange rates.
Keywords: Small Open Economies (SOE); Ireland